Iron depletion is a novel therapeutic strategy to target cancer stem cells - Ninomiya, Takayuki (Oncotarget, 2017)
Adequate iron levels are essential for human health. However, iron overload can act as catalyst for the formation of free radicals, which may cause cancer. Cancer stem cells (CSCs), which maintain the hallmark stem cell characteristics of self-renewal and differentiation capacity, have been proposed as a driving force of tumorigenesis and metastases. In the present study, we investigated the role of iron in the proliferation and stemness of CSCs, using the miPS-LLCcm cell model. Although the anti-cancer agents fluorouracil and cisplatin suppressed the proliferation of miPS-LLCcm cells, these drugs did not alter the expression of stemness markers, including Nanog, SOX2, c-Myc, Oct3/4 and Klf4. In contrast, iron depletion by the iron chelators deferasirox and deferoxamine suppressed the proliferation of miPS-LLCcm cells and the expression of stemness markers. In an allograft model, deferasirox inhibited the growth of miPS-LLCcm implants, which was associated with decreased expression of Nanog and Sox2. Altogether, iron appears to be crucial for the proliferation and maintenance of stemness of CSCs, and iron depletion may be a novel therapeutic strategy to target CSCs.